Dopant‐Induced Giant Photoluminescence of Monolayer MoS2 by Chemical Vapor Transport. Issue 25 (7th August 2022) - Ma, Zhao; Ren, Caixia; Wu, Yu; Qiu, Hailong; Liu, Hongjun; Hu, Zhanggui; Wu, Yicheng
Abstract: Substitutional doping of 2D transition metal dichalcogenides (TMDCs) has been recognized as a promising strategy to tune their optoelectronic properties for a wide array of applications. However, controllable doping of TMDCs remains a challenging issue due to the natural doping of these materials. Here, the controllable growth of Ti‐doped MoS2 monolayers is demonstrated via the chemical vapor transport method, and the atomic embedded structure is confirmed by scanning transmission electron microscope with a probe corrector measurements. Furthermore, the grown Ti‐doped MoS2 monolayer exhibits giant photoluminescence (PL), 85‐fold stronger than a pristine MoS2 monolayer prepared by the same method. The giant PL enhancement is attributed to dopant‐induced O‐Ti‐S units and improved interaction between the monolayer and the mica substrate, increasing the photoluminescence quantum yield and facilitating radiation recombination. The successful growth of Ti‐doped MoS2 monolayer and the improvement of its optical and electrical properties by Ti doping may provide a promising method to engineer the optoelectronic properties of 2D TMDCs materials. Abstract : The Ti‐doped MoS2 monolayers with ultra‐high photoluminescence (PL) intensity are successfully synthesized through chemical vapor transport. The PL intensity from the Ti‐doped MoS2 is 85‐fold stronger than that from the pristine MoS2 . The giant PL enhancement is attributed to dopant‐induced O‐Ti‐S units and improved interaction between the monolayer and the mica substrate, increasing the PLQY and suppressing the nonradiative recombination. These results provide a new route of structural modification for 2D materials and pave the way for applying TMDCs to develop high‐performance optoelectrical devices and electronic components.